Analysis of Micromanagement Strategies in MSMEs in the Digital Era - Mardiah, Ainil; Afrizal, Afrizal; Amalia, Fisy; Fatchuroji, Acep; Muhammad Sabir (Jurnal Economic Resource, 2025)
The purpose of this study is to analyze micromanagement strategies in MSMEs in the digital era. This research approach collects data through a literature review, which involves reading literature from various sources, including books, reports, articles, and journals, employing both qualitative and deductive methods. The results of this study suggest that in the digital era, MSMEs must adopt micromanagement strategies to enhance competitiveness and operational efficiency. These strategies include operational optimization through technology, digital marketing based on social media and e-commerce, financial management utilizing digital applications, and enhancing human resources and leadership through digital literacy. The utilization of consumer data also drives innovation in products and services. The successful implementation of this strategy is supported by the synergy of the digital ecosystem, including the active role of the government, technology platforms, universities, communities, and local media and influencers in providing access, mentoring, and sustainable promotion for MSMEs.